The Results of Nephroblastoma Treatment in Children: Experience of the National Children’s Medical Center and Prospects for Personalized Therapy (Herald of the National Children's Medical Center, 2025)
Background. To evaluate the effectiveness of combined therapy for nephroblastoma in children, including chemotherapy, surgical intervention, and radiotherapy, and to examine prognostic factors affecting patient survival.Materials and methods. The study was conducted as a retrospective cohort analysis involving 45 pediatric patients with histologically confirmed nephroblastoma, treated at the National Children’s Medical Center from January 2021 to March 2025. All patients underwent diagnostics using ultrasonography, multi-slice CT, PET/CT, and MRI. Treatment included radical nephrectomy with lymphadenectomy and adjuvant chemotherapy according to international protocols.Results. The 3- and 5-year overall survival rates were 85.6%. Disease recurrence was observed in 2.2% of patients. Metastasis occurred in 15.5% of cases, including isolated lung involvement (6.6%) and retroperitoneal lymph nodes (4.4%). The mortality rate was 15.5%, with 71.4% of deaths associated with poorly differentiated tumors (G3). Poorly differentiated tumors (G3) were associated with an increased risk of metastasis (OR=3.8, p=0.021). Early-stage disease was associated with better outcomes.Conclusion. Combined therapy for nephroblastoma, including surgery, chemotherapy, and selective radiotherapy, provided a high survival rate (85.6%) in children. However, poorly differentiated tumors are linked to a worse prognosis and a higher risk of metastasis. Early detection of the disease, as well as a personalized approach based on molecular genetic profiling, can improve treatment outcomes.
Keywords: nephroblastoma; chemotherapy; surgery; radiotherapy; survival; metastasis; histological differentiation; personalized therapy